2019
DOI: 10.1027/1864-1105/a000234
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Associations Among Psychological Issues and Problematic Use of Smartphones

Abstract: Abstract. One of the critical limitations of previous research on the association between problematic use of media and psychological factors is that the proposed causality between them is mostly based on cross-sectional data. Responding to this limitation, the present study investigated longitudinal causality associations among loneliness, problematic use of smartphones, face-to-face interaction, smartphone-mediated communication, and need for social assurance with cross-lagged panel models. The results sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 55 publications
0
27
0
Order By: Relevance
“…A massive majority of the retrieved studies had cross-sectional design. Only 14 studies, i.e., about 5% [26,65,95,123,132,144,148,156,184,249,268,269,274,286], were identified as having any form of longitudinal design, test-retest reliability studies excepted.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A massive majority of the retrieved studies had cross-sectional design. Only 14 studies, i.e., about 5% [26,65,95,123,132,144,148,156,184,249,268,269,274,286], were identified as having any form of longitudinal design, test-retest reliability studies excepted.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding psychological factors, several cross-sectional studies found associations between problematic mobile phone use and loneliness [24,91,98,129,133,158,270,279]. A longitudinal study with 288 participants 13–40 years of age examined causal relations between problematic use, loneliness, face-to-face-interaction, and the need for social assurance [132]. It found that loneliness predicted problematic use, while problematic use did not predict loneliness at the follow-up after four months.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Poor communication skills were shown in Medical students who preferred to communicate emotions through texting rather than verbal communication (25) and they correlated with excessive smartphone use (26). Excessive use of the smartphone has negative impacts on people's lives by reducing face-to-face interactions, and increasing loneliness (27).…”
Section: Insecure Attachment Poor Cognitive-emotional Regulation and Communication Problemsmentioning
confidence: 99%
“…10,[31][32][33] Although the only longitudinal study thus far found no evidence for an increase of loneliness, 34 the author argued that excessive use leads users to put less effort to build meaningful relationships, which might ultimately increase loneliness. 34 Moreover, a recent longitudinal study found that heavy Facebook use resulted in higher loneliness, while low to moderate levels of Facebook use even decreased loneliness. 35 We assumed that using the smartphone excessively might have detrimental consequences for (faceto-face) communication with close ties and therefore increase loneliness.…”
Section: Excessive Smartphone Use and Lonelinessmentioning
confidence: 99%